Analysis on Kinematics of 3-PRP Planar Parallel Mechanism - Dong Qianwen; Liu Yongjiang; Li Ruiqin; Jiang Hongjun (Jixie chuandong)
A kind of 3-DOF planar parallel mechanism which has two translational and one rotational is introduced.Firstly,the position and posture analysis of the parallel mechanism is conducted,its positive and inverse solution equations are established,and then the position positive and inverse solution are solved.Secondly,by using the MATLAB to calculate a group of experimental data,the results can be used to test the correctness of equations.At last,according to the positive and inverse solutions equations,the velocity and acceleration of mechanism input and output are solved.The results show that the structure of 3-PRP mechanism is simple and also can be easy to control and drive,meanwhile,the researching results established a certain theoretical basis for the performance research on the mechanism such as workspace,trajectory planning and optimum design.